Sex determination from metopic suture and supraorbital ridge in Thai population - Duangto, Phuwadon; Mahiphot, Jarupon; Chompoopheun, Hathaichanok; Mahakkanukrauh, Pasuk (Biomedical Sciences and Clinical Medicine, 2024)
Objectives This study was carried out on metopic suture and supraorbital ridge for sexing in a Thai population. Materials and methods This study included 300 human adult skulls, which were obtained from the Forensic Osteology Research Center, Faculty of Medicine, Chiang Mai University. The metopic suture and supraorbital ridge were observed macroscopically. The degree of supraorbital ridge was classifi ed into 4 levels. The 1st level had a massive prominence, the 2nd showed fair prominence, the 3rd indicated slight prominence and the 4th revealed no prominence. Descriptive statistics were analyzed by the SPSS program. Results The metopic suture can be divided into three groups: 1) normal skulls without metopic suture, of which 12.9% were male and 87.1% female, 2) skulls with complete metopic suture in 75% male and 25% female, and 3) skulls with incomplete metopic suture with 68.9% male and 31.1% female. Furthermore, sex determination from study of the supraorbital ridge showed major percentages in the male skull of 94.5% and 93.9% at the 1st and 2nd level, respectively. Female skulls showed major percentages of 76% and 92% at the 3rd and 4th level, respectively. Conclusion Metopic suture and supraorbital ridge could be bony landmarks for sex determination and biological identifi cation in a Thai population.